The Dollar as a Reserve Currency: An Address - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "The Dollar as a Reserve Currency: An Address," written by Walter B. Wriston for the 38th Annual Meeting of the Bankers' Association of Foreign Trade on 2 May 1960. The original speech is located in MS134.001.001.00011.